2013
DOI: 10.3389/fnins.2013.00095
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative multi-parameter mapping of R1, PD*, MT, and R2* at 3T: a multi-center validation

Abstract: Multi-center studies using magnetic resonance imaging facilitate studying small effect sizes, global population variance and rare diseases. The reliability and sensitivity of these multi-center studies crucially depend on the comparability of the data generated at different sites and time points. The level of inter-site comparability is still controversial for conventional anatomical T1-weighted MRI data. Quantitative multi-parameter mapping (MPM) was designed to provide MR parameter measures that are comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

36
671
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 478 publications
(708 citation statements)
references
References 60 publications
36
671
1
Order By: Relevance
“…Multiband (MB) factors of 1, 2, 4, and 8 were used. As the TR was reduced with increasing MB factor, the flip angle was optimized to match the Ernst angle based on a grey matter (GM) T1 value of 1,000 ms at 3 T (Weiskopf et al, 2013). All multiband RF excitations were performed with MB RF Phase Scramble selected (Wong 2012) and the data were reconstructed using the MB LeakBlock Kernel option (Cauley et al, 2014), which has been shown to suppress residual aliasing of BOLD signal across slices in fMRI (Risk, Kociuba, & Rowe, 2018; Todd et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Multiband (MB) factors of 1, 2, 4, and 8 were used. As the TR was reduced with increasing MB factor, the flip angle was optimized to match the Ernst angle based on a grey matter (GM) T1 value of 1,000 ms at 3 T (Weiskopf et al, 2013). All multiband RF excitations were performed with MB RF Phase Scramble selected (Wong 2012) and the data were reconstructed using the MB LeakBlock Kernel option (Cauley et al, 2014), which has been shown to suppress residual aliasing of BOLD signal across slices in fMRI (Risk, Kociuba, & Rowe, 2018; Todd et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Both processes are enhanced by the presence of macromolecular content (eg, myelin). As such, they are sensitive to tissue microstructure and provide quantitative measures that can be used for multicenter studies and give information about myelin, water, and iron content 33. All image volumes were checked for artifacts.…”
Section: Methodsmentioning
confidence: 99%
“…All scans were acquired using the MPM sequence (31) implemented on three identical 3T whole-body MRI systems (Magnetom TIM Trio; VB17 software version; Siemens Healthcare): two located in Cambridge and one located in London. Between-site reliability and tolerability of all MRI procedures were satisfactorily assessed by a pilot study of five healthy volunteers each scanned for ∼25 min at each site (31). The between-site bias was less than 3% and the between-site coefficient of variation was less than 8% for both longitudinal relaxation rate (R1) and MT parameters (31).…”
Section: Methodsmentioning
confidence: 99%
“…Between-site reliability and tolerability of all MRI procedures were satisfactorily assessed by a pilot study of five healthy volunteers each scanned for ∼25 min at each site (31). The between-site bias was less than 3% and the between-site coefficient of variation was less than 8% for both longitudinal relaxation rate (R1) and MT parameters (31). R1 and MT were quantified in Matlab (The MathWorks, Inc.) using SPM8 (www.…”
Section: Methodsmentioning
confidence: 99%